2017
DOI: 10.1016/j.trecan.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

NLRC5/CITA: A Key Player in Cancer Immune Surveillance

Abstract: Cancer cells need to escape immune surveillance for successful tumor growth. Loss of MHC class I has been described as a major immune evasion strategy in many cancers. MHC class I transactivator (CITA), NLRC5, has found to be a key transcription coactivator of MHC class I genes. Recent genetic studies revealed that NLRC5 is a major target for cancer immune evasion mechanism. The reduced expression or activity of NLRC5 caused by promoter methylation, copy number loss, or somatic mutations is associated with def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
55
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 85 publications
(131 reference statements)
1
55
0
Order By: Relevance
“…FOXK1 has been determined to process the pivotal role in the etiology of many cancers [18]. There is an elevated expression of FOXK1 in breast cancer, and it could promote cell proliferation and migration [19].…”
Section: Discussionmentioning
confidence: 99%
“…FOXK1 has been determined to process the pivotal role in the etiology of many cancers [18]. There is an elevated expression of FOXK1 in breast cancer, and it could promote cell proliferation and migration [19].…”
Section: Discussionmentioning
confidence: 99%
“…One example that potentially contributes to the immunosuppressive phenotype found in G3 is the highly expressed mir-149, which has already been reported as dysregulated in many types of cancer including melanoma, where its upregulation influences the expression of both oncogenes and tumor suppressor genes [48]. In this study, we showed that the inhibition of its target, NLRC5, interferes with neo-antigen presentation, in agreement with other studies where it has been associated with immune evasion mechanisms and considered as a biomarker of immune surveillance [18].…”
Section: Discussionsupporting
confidence: 91%
“…It is well known that mutation and neoantigen burden are positively correlated to immunogenicity [17], however, although G2 and G3 show similar mutation and neoepitope burden and share the same mutational signature profile, they present different immunogenic profiles. Four different findings suggested immune evasion mechanisms in G3: [1] the stronger signature of checkpoint molecules which could induce T-cell exhaustion or compromise leukocyte activation and impair the supported anti-tumor immune response [46]; the suppression of antigen processing and presenting pathway, evidenced by [2] the higher dissociation constant (KD) of neoepitopes that diminishes antigen:HLA-I stability, which has been previously observed in other studies [47] and [3] the higher frequency of neoantigens in samples bearing mutations in the antigen processing and presenting pathway; [4] and downregulation of genes related to antigen presentation [17][18][19].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…18,47 Additionally, NLRC5 is a critical player in maintaining immune surveillance. 16,48 For now, the biological function of IFIT5 remains elusive, recently one study found it was associated with epithelial to mesenchymal transition in renal cancer, but its potential role in immune regulation should be fully explored in tumors, especially in glioma. 49 Then we performed protein-protein interactions based on STRING database, 50 the results showed that IFIT5 may interact with some genes which exerts pivotal role in the IFN mediated signaling.…”
Section: Discussionmentioning
confidence: 99%